Alloimmunization is associated with older age of transfused red blood cells in sickle cell disease. Issue 8 (28th May 2015) - Desai, Payal C.; Deal, Allison M.; Pfaff, Emily R.; Qaqish, Bahjat; Hebden, Leyna M.; Park, Yara A.; Ataga, Kenneth I.
<x xml:space="preserve">Abstract</x> Red blood cell (RBC) alloimmunization is a significant clinical complication of sickle cell disease (SCD). It can lead to difficulty with cross‐matching for future transfusions and may sometimes trigger life‐threatening delayed hemolytic transfusion reactions. We conducted a retrospective study to explore the association of clinical complications and age of RBC with alloimmunization in patients with SCD followed at a single institution from 2005 to 2012. One hundred and sixty six patients with a total of 488 RBC transfusions were evaluated. Nineteen patients (11%) developed new alloantibodies following blood transfusions during the period of review. The median age of RBC units was 20 days (interquartile range: 14–27 days). RBC antibody formation was significantly associated with the age of RBC units (P = 0.002), with a hazard ratio of 3.5 (95% CI: 1.71–7.11) for a RBC unit that was 7 days old and 9.8 (95% CI: 2.66–35.97) for a unit that was 35 days old, 28 days after the blood transfusion. No association was observed between RBC alloimmunization and acute vaso‐occlusive complications. Although increased echocardiography‐derived tricuspid regurgitant jet velocity (TRV) was associated with the presence of RBC alloantibodies (P = 0.02), TRV was not significantly associated with alloimmunization when adjusted for patient age and number of transfused RBC units. Our study suggests that RBC antibody formation is significantly associated with older age of RBCs at the time of transfusion. Prospective studies in patients with SCD are required to confirm this finding. Am. J. Hematol. 90:691–695, 2015. © 2015 Wiley Periodicals, Inc.